Analisis Kinerja Pelayanan Koperasi Kerta Semaya Samaniya terhadap Kepuasan Petani Kakao di Desa Nusasari Kecamatan Melaya Kabupaten Jembrana - NOVITASARI, DWI; SUSRUSA, KETUT BUDI; DARMAWAN, DWI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Performance Analysis of Kerta Semaya Samaniya Cooperative Services on Cocoa Farmers Satisfaction in Nusasari Village, Melaya District, Jembrana Regency Service performance of the production business unit run by the Kerta Semaya Samaniya (KSS) Cooperative together with the Kalimajari Foundation through the Kakao Lestari program has certainly provided many benefits and will certainly affect the satisfaction of the members. This study aims to determine the members' assessment of the service performance of the KSS Cooperative in the production business unit, and to determine the level of satisfaction of cocoa farmers as members of the KSS Cooperative and policy solutions in improving services to members. The study uses simple random sampling with a number of 55 people who were distributed proportionally. The analysis method used is descriptive analysis, member satisfaction index and importance performance analysis. Based on the results, the members' assessment on the level of importance has one indicator that is considered not very important, while the other three indicators are considered important. Assessment on the performance level shows three indicators that are considered to have low performance, while the other four indicators are considered to have good performance. The level of satisfaction based on the member satisfaction index shows that the members are quite satisfied with the current KSS cooperative service performance. Policy solutions that can be done in order to improve service quality are by making improvements to the indicators that are included in quadrant A (top priority) in the IPA diagram.